2021
DOI: 10.1007/s13399-021-02007-6
|View full text |Cite
|
Sign up to set email alerts
|

Bioprocessing of fermentable sugars derived from water hyacinth into microbial lipids and single cell proteins by oleaginous yeast Rhodosporidium toruloides NCIM 3547

Abstract: In this study we employed microwave-acid pretreatment for water hyacinth (WH) to obtain liquid hydrolysate that contains sugars derived from holocellulosic components of biomass for further oleaginous yeast fermentation. In order to remove the inhibitors such as furans after acid treatment, detoxification of hydrolysate was done and we compared the efficiency of this step with non-detoxified hydrolysate towards capability of the Rhodosporidium toruloides NCIM 3547 (an oleaginous yeast) to produce microbial lip… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 85 publications
(104 reference statements)
0
13
0
Order By: Relevance
“…(formerly known as Rhodosporidium), Yarrowia lipolytica, and Lipomyces sp. Interestingly, the oleaginous yeast Rhodosporidium toruloides was considered an industrial potential single-cell microbe that showed a high potential to accumulate higher amounts of lipids that were used as a feedstock for biodiesel production [53][54][55]. In the current investigation, we aimed to optimize lipid accumulation by the yeast isolate Rhodotorula toruloides Y1124 using the Plackett-Burman design and central composite design in order to maximize the lipid accumulation capability by the oleaginous yeast for biodiesel production.…”
Section: Discussionmentioning
confidence: 99%
“…(formerly known as Rhodosporidium), Yarrowia lipolytica, and Lipomyces sp. Interestingly, the oleaginous yeast Rhodosporidium toruloides was considered an industrial potential single-cell microbe that showed a high potential to accumulate higher amounts of lipids that were used as a feedstock for biodiesel production [53][54][55]. In the current investigation, we aimed to optimize lipid accumulation by the yeast isolate Rhodotorula toruloides Y1124 using the Plackett-Burman design and central composite design in order to maximize the lipid accumulation capability by the oleaginous yeast for biodiesel production.…”
Section: Discussionmentioning
confidence: 99%
“…Another research has evaluated the bioconversion of fermentable sugars derived from WH into microbial lipids and single cell proteins by an oleaginous yeast. This study indicated the feasibility of sustainable valorization of WH-derived liquid hydrolysate towards a biorefinery framework Alankar et al (2021). By the way, Arutselvy et al (2020), have conducted a sequential valorization strategy for dairy wastewater (DW) and WH to produce fuel and fertilizer.…”
Section: Valorization Of Whmentioning
confidence: 95%
“…In another study, water hyacinth was initially subjected to microwave‐acid pre‐treatment for obtaining liquid hydrolysate containing sugars derived from holocellulosic components of the biomass. This hydrolysate was further subjected to fermentation for the production of microbial lipids and single cell protein using the oleaginous yeast Rhodosporidium toruloides NCIM 3547 71 . After pre‐treatment, the inhibitors such as furans were detoxified using the over‐liming process and both the detoxified and non‐detoxified hydrolysates were used for the production of microbial lipids and single‐cell proteins.…”
Section: Aquatic Biomass Biorefineriesmentioning
confidence: 99%
“…This hydrolysate was further subjected to fermentation for the production of microbial lipids and single cell protein using the oleaginous yeast Rhodosporidium toruloides NCIM 3547. 71 After pre-treatment, the inhibitors such as furans were detoxified using the over-liming process and both the detoxified and non-detoxified hydrolysates were used for the production of microbial lipids and single-cell proteins. The results indicated that the reducing sugar concentration was found to be higher in the nondetoxified hydrolysate (65.41 g L −1 ) than the detoxified one (59.18 g L −1 ).…”
Section: Water Hyacinth-based Biorefineriesmentioning
confidence: 99%
See 1 more Smart Citation